Report on the Annual Gametogenesis and Tissue Biochemical Composition in the Gray mussel, Crenomytilus grayanus (Dunker 1853) in the Subtidal Rocky Bottom on the East Coast of Korea - Subramaniam, T.; Hee‑Jung Lee; Hee‑Do Jeung; Hyun‑Sil Kang; Chul‑Won Kim; Hyung‑Seop Kim; Young‑Ghan Cho; Kwang‑Sik Cho (Ocean Science Journal, 2021)
The Gray mussel Crenomytilus grayanus occurs in high density in the shallow rocky subtidal zone on the east coast of Korea, where the mussel dominates the shallow subtidal benthic community. In this study, we frst examined the annual gametogen esis and temporal changes in the tissue composition, which provides crucial information to the management of the mussel on the east coast. Based on histological analysis, oogenesis and spermatogenesis commenced in September, as the small oogonia (16.67±4.87 µm in diameter) and spermatogonia developed on the follicle walls, respectively. In March, the mature oocytes (46.55±9.91 µm in diameter) and spermatozoa dominated the follicle. During May and June, most of the males and females spawned when the surface seawater temperature (SST) increased from 15.5 to 22.3 °C. The total carbohydrate level in the tissue increased dramatically from April to May, which coincided with the chlorophyll-a maximum occurring in April. Condition index, a ratio of tissue weight to shell weight, also increased from February to May and then declined in June, suggesting that most mussels released the gametes through spawning during these months. Our data suggest that C. grayanus is a spring spawner, and the onset of gametogenesis and subsequent spawning is closely linked to the seasonal changes in the water temperature and food availability in the water column.
Keywords: Crenomytilus grayanus; East Coast of Korea; Gametogenesis; Gray mussel; Spring spawner; Total Carbohydrate